Subject and Abject: TikTok as a Playing Space in Constructing Self-Identity for Women in the Digital Era - Kurniawati, Juliana; Sudahri, Ari (Jogjakarta Communication Conference (JCC), 2025)
This article examines the role of TikTok as a playing space in relation to women's identity construction, focusing on the concept of